2017
DOI: 10.1093/jnen/nlw105
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Brain Soluble Tau and the Tau Secretion Factor

Abstract: Neurofibrillary tangles (NFTs) represent products of insoluble tau protein in the brains of patients with Alzheimer disease (AD). The cerebrospinal fluid (CSF) tau level is a biomarker in AD diagnosis. The soluble portion of tau protein in brain parenchyma is presumably the source for CSF tau but this has not previously been quantified. We measured CSF tau and soluble brain tau at autopsy in temporal and frontal brain tissue samples from 7 cognitive normal, 12 mild cognitively impaired, and 19 AD subjects. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…Among other clinical criteria 33 , CSF biomarkers are required in the determination of MCI due to AD, such as CSF Aβ 1-42 , total-Tau, and/or p-Tau concentrations 32 . Several studies in the literature have shown a significant difference in CSF Aβ 1-42 [34][35][36] , total-Tau [35][36][37][38][39] , and p-Tau 37 concentrations between MCI and AD patients, describing a decrease in the CSF Aβ 1-42 concentration ([Aβ 1-42 ] CSF ) and an increase in the CSF total-Tau and p-Tau concentrations ([Tau] CSF and [p-Tau] CSF ) in AD patients. However, these differences are not always statistically significant for CSF Aβ 1-42 37,40 , total-Tau 34,40 , and p-Tau 34,35,39,40 .…”
Section: Early Stage Of Ad: Csf and Plasma Biomarkersmentioning
confidence: 99%
“…Among other clinical criteria 33 , CSF biomarkers are required in the determination of MCI due to AD, such as CSF Aβ 1-42 , total-Tau, and/or p-Tau concentrations 32 . Several studies in the literature have shown a significant difference in CSF Aβ 1-42 [34][35][36] , total-Tau [35][36][37][38][39] , and p-Tau 37 concentrations between MCI and AD patients, describing a decrease in the CSF Aβ 1-42 concentration ([Aβ 1-42 ] CSF ) and an increase in the CSF total-Tau and p-Tau concentrations ([Tau] CSF and [p-Tau] CSF ) in AD patients. However, these differences are not always statistically significant for CSF Aβ 1-42 37,40 , total-Tau 34,40 , and p-Tau 34,35,39,40 .…”
Section: Early Stage Of Ad: Csf and Plasma Biomarkersmentioning
confidence: 99%
“…This was particularly evident in the proteomics data, where levels of sarkosyl-insoluble total tau were not different between APP swe / PS1 ΔE9 and control mice, but were > 30-fold elevated in AD vs. non-AD subjects. Studies estimating 65 and measuring 66 the amount of insoluble tau protein in the human AD brain show that tau levels are significantly higher than control in symptomatic AD patients, but not in patients with prodromal or preclinical AD. It might thus be that the tau pathology we detect in APP swe / PS1 ΔE9 mice corresponds to early stage AD.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to Aβ, the vast majority of tau protein can be isolated within aqueous or detergent soluble fractions. In non-AD cases, as much as 97% of tau can be recovered from the soluble fraction, whilst in AD this is considerable lower (~50%) due to the accumulation of insoluble aggregates (Mukaetova-Ladinska et al, 1993;Tremblay et al, 2007;Han et al, 2017). Insoluble tau isolated from human AD brains is 3-4-fold higher compared to non-AD brains (Hanger et al, 1991;Ksiezak-Reding et al, 1992) and levels within temporal and parietal regions are robustly elevated mirroring the regional burden of NFTs.…”
Section: Introductionmentioning
confidence: 99%